Basic butterfly swimming technique - Wender, Michael (Monterey, CA : Coaches Choice, 2005)
Features a progressive system of skills and drills designed to perfect the basic elements of successful and efficient swimming. Step-by-step instructions are explained in detail in an easy-to-understand and apply manner
Title from title screen
Instructor/coach: Michael'Mickey' Wender
Keywords: Swimming -- Butterfly stroke; Swimming -- Training; Instructional videos